APPROACH OF A PROCESS IN LEARNING MATERIALS OF ESSAY WRITING AS AN EFFORT TO INCREASE STUDENT’S WRITING SKILL - Nur Ihsan Halil (Universitas Sembilanbelas November Kolaka, 2016)
Although the writing skills in the Indonesian language has been taught formally starting from the seventh grade junior high school to twelfth grade to senior school, new students' writing skills of the Indonesian Language Education and Literary Study Program, Universitas Sembilanbelas November Kolaka in average remains low. The results of writing tests conducted in the course writing of second semester indicated that the poor writing skills of students especially the essay writing skills. The average writing scores obtained did not reach 62. In other words, when given a letter grade, the average ability of the new student was at a value C. This is still relatively low because the average minimum expected is 65 or B. Learning to write an essay with the process approach is seen as an approach that can provide a solution. Therefore, this approach emphasizes the writing process, which is divided into three activities, namely activities before writing, writing activities, and activities after writinG.